Pengaruh Gaya Kepemimpinan Transformasional Terhadap Kinerja Melalui Motivasi dan Lingkungan Kerja - Rismawati; Sobari, Yayat; Utomo, Kabul Wahyu (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2025)
This study is to analyze the Influence of Transformational Leadership Style on Employee Performance Through Motivation and Work Environment (Study at the Bandung Cibeunying Pratama Tax Service Office in 2022). This research was conducted at the Bandung Cibeunying Primary Tax Service Office in 2022. This research is descriptive with a quantitative approach. Samples were taken using the saturated sampling technique, with a sample of 115 respondents. The method of collecting data related to the research problem was carried out using the questionnaire method. The analysis in this study uses PLS. The results of the study show that Transformational Leadership has a significant effect on work motivation, Transformational leadership has a significant effect on work motivation, work motivation has a significant effect on employee performance, the work environment is not significant in improving performance, external motivation has an effect on the work environment, work motivation has a positive and significant effect on the work environment and transformational leadership has a significant effect on the work environment. Performance.